2017
DOI: 10.1111/echo.13789
|View full text |Cite
|
Sign up to set email alerts
|

Significance of isolated papillary muscle hypertrophy: A comparison of left ventricular hypertrophy diagnosed using electrocardiography vs echocardiography

Abstract: Isolated papillary muscle hypertrophy can cause ECG abnormalities such as LV high voltage and LV strain pattern. Particular attention must be paid to the papillary muscle during echocardiographic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other studies that investigated the prognostic significance of fQRS reported that the presence of fQRS was associated with a significant increase in arrhythmic events in HCM patients (Femenia et al., 2013; Ozyilmaz et al., 2017). Strain pattern is a known ECG sign of HCM and is associated with a higher cardiovascular risk and abnormal left ventricular function (Goldberger, 1979; Nomura et al., 2018; Ogah et al., 2008). It is also known that ECG strain is a marker of myocardial fibrosis in aortic stenosis and in hypertension (Rodrigues et al., 2017; Shah et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that investigated the prognostic significance of fQRS reported that the presence of fQRS was associated with a significant increase in arrhythmic events in HCM patients (Femenia et al., 2013; Ozyilmaz et al., 2017). Strain pattern is a known ECG sign of HCM and is associated with a higher cardiovascular risk and abnormal left ventricular function (Goldberger, 1979; Nomura et al., 2018; Ogah et al., 2008). It is also known that ECG strain is a marker of myocardial fibrosis in aortic stenosis and in hypertension (Rodrigues et al., 2017; Shah et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we demonstrate the suppressive function of PRMT7 in the cardiac hypertrophic response. Maladaptive cardiac hypertrophy in disease conditions is accompanied by alterations in the contractile properties with the expression of fetal contractile genes and increased expression of extracellular matrices, such as collagens and bronectins [30][31][32]. PRMT7 KO cardiomyocytes and acute depletion of PRMT7 in NRVMs exhibited enlarged cell size and alteration in the expression of fetal genes, likely contributing to the decreased cardiac contractile function of PRMT7 cKO mice infused with Ang II.…”
Section: Discussionmentioning
confidence: 99%